The Influence of Metabolic Syndrome and Sex on the DNA Methylome in Schizophrenia - Kyle J. Burghardt; Jacyln M. Goodrich; Brittany N. Lines; Vicki L. Ellingrod (International Journal of Genomics)
Introduction. The mechanism by which metabolic syndrome occurs in schizophrenia is not completely known; however, previous work suggests that changes in DNA methylation may be involved which is further influenced by sex. Within this study, the DNA methylome was profiled to identify altered methylation associated with metabolic syndrome in a schizophrenia population on atypical antipsychotics. Methods. Peripheral blood from schizophrenia subjects was utilized for DNA methylation analyses. Discovery analyses (n=96) were performed using an epigenome-wide analysis on the Illumina HumanMethylation450K BeadChip based on metabolic syndrome diagnosis. A secondary discovery analysis was conducted based on sex. The top hits from the discovery analyses were assessed in an additional validation set (n=166) using site-specific methylation pyrosequencing. Results. A significant increase in CDH22 gene methylation in subjects with metabolic syndrome was identified in the overall sample. Additionally, differential methylation was found within the MAP3K13 gene in females and the CCDC8 gene within males. Significant differences in methylation were again observed for the CDH22 and MAP3K13 genes, but not CCDC8, in the validation sample set. Conclusions. This study provides preliminary evidence that DNA methylation may be associated with metabolic syndrome and sex in schizophrenia.